Budaya Organisasi dan Kepemimpinan dalam Pengelolaan Piutang Pajak Impor - Amrie Firmansyah; Ria Dewi Ambarwati; Wing Hartopo; Iis Iswandy (Studi Akuntansi dan Keuangan Indonesia, 2022)
This study examines organizational culture and leadership on tax revenue receivables management in the context of imports. The data used in this study derives from a questionnaire survey distributed to respondents from March to July 2022. The respondents for this study were selected using purposive sampling with the criteria is officials/employees at the Treasury Unit who manage tax receivables and Officers/employees at the General Affairs/Finance Unit, which handles the Financial Statements in each work unit within DGCE. The final sample used in this study totaled 166 observations. This study concludes that organizational culture positively affects the management of tax revenue receivables in the context of imports, while leadership does not affect the management of tax revenue receivables in the context of imports.